'I don't want them to feel like we're part of the establishment': teachers' learning to work with refugee families as entangled becomings. Issue 2 (27th May 2021) - Kendall, Alexandra; Puttick, Mary-Rose; Wheatcroft, Louise
ABSTRACT: In this paper we 'plug in' ideas from post-qualitative thinking to read empirical material from Erasmus+ project, Open School Doors, and mobilise new ways of conceptualising teachers' work with newly arrived families. Driven by commitments to inclusion and social justice teacher participants described tacit, in-the-moment, knowledge-making, that felt contingent and risky, as they sought to respond to encounters with families that demanded compassionate action but pushed them beyond the threshold of professional certainty and the would-be neutralities of 'professional' identities. We understand these affective responses to the work of teaching as 'abductive' moments of breakdown, rupture and estrangement, that draw attention to the always already becoming nature of professional practice. We put to work the concepts of entanglement, assemblage and rhizomes to make use of 'abductive' moments as productive opportunities for exploration of teachers' messy, implicated, intra-relatedness to their practice worlds and to imagine models of professional learning that promote connection and knowledge-in-the-making as ethical, 'response-able' post/rhizo-professional alternative to linear forms of professional learning. Our discussion is embedded in a specific context but has important broader implications for the design of teacher education as preparation for complex anticipated working lives.